Nonalcoholic fatty liver disease and osteoporosis: A potential association with therapeutic implications. Issue 9 (14th June 2022) - Vachliotis, Ilias D.; Anastasilakis, Athanasios D.; Goulas, Antonis; Goulis, Dimitrios G.; Polyzos, Stergios A.
Abstract: Nonalcoholic fatty liver disease (NAFLD) and osteoporosis are two highly prevalent metabolic diseases. Increasing experimental evidence supports a pathophysiological link between NAFLD and osteoporosis. A key feature could be chronic, low‐grade inflammation, which characterizes NAFLD and possibly affects bone metabolism. In this context, several factors, including but not limited to receptor activator of nuclear factor kappa‐B ligand, osteoprotegerin, osteopontin and osteocalcin, may serve as mediators. In the clinical setting, most but not all epidemiological evidence indicates that NAFLD is associated with lower bone mineral density or osteoporosis in adults. Although an association between NAFLD and osteoporosis has not yet been established, and thus remains speculative, pharmacological considerations already exist. Some of the current and emerging pharmacological options for NAFLD have shown possible anti‐osteoporotic properties (eg, vitamin E, obeticholic acid, semaglutide), while others (eg, pioglitazone, canagliflozin) have been associated with increased risk of fractures and may be avoided in patients with NAFLD and concomitant osteoporosis, especially those at high fracture risk. Conversely, some anti‐osteoporotic medications (denosumab) might benefit NAFLD, while others (raloxifene) might adversely affect it and, consequently, may be avoided in patients with osteoporosis and NAFLD. If an association between NAFLD and osteoporosis is established, a medication that could target both diseases would be a great advancement. This review summarizes the main experimental and clinical evidence on the potential association between NAFLD and osteoporosis and focuses on treatment considerations derived from this potential association.